Information Services in Evidence Based Medical Education: A Review of Implementation Trends - Khani, Sedigheh; Panahi, Sirous; Pirsalehi, Ali; Pourabbasi, Ata (Evidence Based Library and Information Practice, 2021)
Objective – Evidence based medical education requires supportive information services to facilitate access to the needed educational evidence. Information services designed specifically for evidence based medical education are limited or locally developed for educational units. For librarians to have an opportunity to cooperate efficiently with medical educators in evidence based medical education, they require an empirical prototype for transmission of clinical evidence at the right place and the right time. Therefore, there is a need to recognize types of information services which support evidence based medical education. The purpose of this review is to identify implementation trends of evidence based educational information services. Methods – We found related studies by implementing search strategies in PubMed, EMBASE, Web of Science, Scopus, LISTA, and Google Scholar with keywords like: evidence based medical education, information services, and library services. We used reference-checking and citation-checking of related articles for completing the process of locating relevant articles. After employing inclusion and exclusion criteria, we selected 11 articles for inclusion in the review and analyzed them using a narrative review technique. Results – After analyzing the results of the included studies, we identified two elements categorized as program development and five elements categorized as implementation trend. Prerequisites of program and the process of designing were essential parts of program development of information services. Schedule and type of access, how to receive educational-clinical questions, information services types, responding time, and providing evidence based outputs were the elements of the implementation process of educational supported information services. Conclusion – Designing an evidence based educational information service strongly depends on the information needs of learners at each educational level. Schedule and type of access to information service, time of responding to the received query, and preparation of evidence based output are essential factors in designing practical educational-developed information services.